Ambuyat Crackers / Yuriqa Abdul Kahar... [et al.] - Abdul Kahar, Yuriqa; Yusop, Nur Nadhira Aeiza; Mohd Farid, Azie; Nicasius, Jane; Hamzah, Nor Ah Merah; Yusop, Nur Nadhira Aeiza (2015)
In this era of modernization, some people might not even know about the existence of ambuyat and what ambuyat taste like especially the young generation has gradually ignored the practice of traditional food. Ambuyat is one of the most popular foods in Sabah and Sarawak and especially to Brunei and local delicacy in the Malaysian states. The satisfaction of traditional food among the Sabahan people was unlimited with the various taste of traditional food. Apart from that, our company which is 6Teens Company decided to create the idea of an Ambuyat Cracker from the waste of ambuyat where we innovate from the originality of ambuyat's taste to various types of ambuyat cracker. Ambuyat crackers were made with many flavor of taste which is black pepper, cheese, and coco. This will be wrapped in single packaging to ensure it is fresh and have high quality. Furthermore, Ambuyat Cracker shop can be found at Lot 1-39, Star City North Complex, 1st Floor, Jalan Asia City, 88100, Kota Kinabalu, Sabah which can attract more customers such as tourist and local people. Hence, Ambuyat Cracker is able to search by our official page that can be found in Facebook, blog and our templates. So, it is convenient visit to those who still seek or might be not familiar with our product of food. In short, Ambuyat Cracker may widen its product to global market due to its uniqueness and tasty.